(untitled) - Cleland, David I. (New York, 2007)
The theme of the last edition will continue as authors improve individual chapters by adding a brief introduction that outlines the central points of the chapter and warms up readers for what follows. Each chapter concludes with four additional sections: a listing of additional sources of information in the form of a generously annotated bibliography; a listing of project management principles that summarize chapter content in pithy statements of enduring, universal value; a project management situation - a brief, descriptive case study that illuminates chapter content by way of a practical example; and a student/reader assignment that offers food for thought, discussion, or investigation. More student problems are added in this edition along with new chapters throughout and up-dated chapters where change is warranted.
Keywords: Project management; Quản lý dự án